2017
DOI: 10.1038/s41522-016-0007-9
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary adaptations of biofilms infecting cystic fibrosis lungs promote mechanical toughness by adjusting polysaccharide production

Abstract: Biofilms are communities of microbes embedded in a matrix of extracellular polymeric substances, largely polysaccharides. Multiple types of extracellular polymeric substances can be produced by a single bacterial strain. The distinct polymer components of biofilms are known to provide chemical protection, but little is known about how distinct extracellular polysaccharides may also protect biofilms against mechanical stresses such as shear or phagocytic engulfment. Decades-long infections of Pseudomonas. aerug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
199
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(220 citation statements)
references
References 60 publications
(61 reference statements)
19
199
2
Order By: Relevance
“…indicates that these bacteria may support the B vitamin requirements of the entire community 61 . A host-associated study evaluated the long-term persistence of the microbiota after faecal transplantation in patients infected with C. difficile 62 and identified Bacteroides spp. as the most common donor microorganism in recipients after transplantation.…”
Section: Network Dynamics and Cross-feedingmentioning
confidence: 99%
“…indicates that these bacteria may support the B vitamin requirements of the entire community 61 . A host-associated study evaluated the long-term persistence of the microbiota after faecal transplantation in patients infected with C. difficile 62 and identified Bacteroides spp. as the most common donor microorganism in recipients after transplantation.…”
Section: Network Dynamics and Cross-feedingmentioning
confidence: 99%
“…Since the tip/sample area increases in principle while indenting, the dependence of force on indentation is nonlinear and described by the Hertz model for small indentations (Supplementary information). Application of this model to the stiff response portion of F vs. Ind curves, corresponding to the second regime, allow estimating the average Young's modulus, E, of the core material of 0.37 ± 0.18 GPa (Table 1), comparable to that of amyloid fibers 35 , which are involved in adhesion of different bacteria 36 or of mussels byssal threads 37 ), but one and two orders of magnitude higher than the EPS from Staphylococcus epidermidis 14 and Pseudomonas aeruginosa 38 , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…It is well-known that increasing the concentration of polymer in a gel will increase the gel's elastic modulus 31 . We varied agarose concentrations from 0.3% -2% and the resulting range of elastic moduli, ~0.1 to ~10 kPa, roughly covered the range of elastic moduli that we measured previously for biofilms grown from clinical isolates of Pseudomonas aeruginosa 18 . The value of the elastic modulus at the midpoint of the plateau region in strain sweeps is the value we will use to characterize these gels' mechanics, unless the material was already yielding for the lowest strain usedin that case, the value of the elastic modulus that was measured at the lowest strain will be used ( Figure 1B).…”
Section: Agarose Gelsmentioning
confidence: 99%
“…Imaging studies of chronic biofilm infections show bacterial aggregates that are densely surrounded by neutrophils that do not enter the aggregates and are unable to clear the infection 12,13 However, biofilms are not rigid solids but are composite viscoelastic materials. We have shown that biofilms re-grown from clinical isolates have elastic moduli in the range ~0.05-10 kPa 18 . We also found that in vivo evolution in chronic Cystic Fibrosis (CF) infections changed the production of matrix polymers in a way that promoted mechanical toughness 18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation